THE IMPACT OF CHAT GPT ON KNOWLEDGE SHARING AMONG LANGUAGE RESEARCH STUDENTS - Telaumbanua, Yasminar Amaerita; Mendrofa, Finci Trisnawati; Larosa, Yulidartini; Harefa, Nurmawati; Tafonao, Ica Murni (STKIP Citra Bakti, 2024)
This study investigates the effect of using Chat GPT on students' ability to share knowledge in a Language Research class at the English Language Education Study Program, Nias University. The research gap lies in the lack of understanding of the specific impact of GPT Chat on knowledge sharing practices in a classroom environment. This study used a correlation quantitative method that used a research instrument which was a 5-point Likert scale questionnaire as distributed to 20 fourth semester B students. Data analysis showed a very strong correlation (r = 0.971) between the use of Chat GPT (mean score 17.4) and knowledge sharing ability (mean score 16.6). Hypothesis testing yielded a value of 0.9735, indicating a statistically significant result. These findings suggest that Chat GPT has a significant influence on students' knowledge sharing ability in Language Research classes, which has important implications for the integration of Al technology in learning. Further research is needed to investigate other aspects of the use of Chat GPT in educational contexts and to develop effective guidelines for its use.